Terrestrial Laser Scanner (TLS) Measurement in A Volcanic Area: Detection of Error Source and Scanned Object Intensity - Nia Haerani; Hasanuddin Z. Abidin; Surono Surono; Dudy D. Wijaya (Indonesian Journal on Geoscience, 2020)
DOI:10.17014/ijog.7.2.179-200The purpose of the study of Terrestrial Laser Scanner (TLS) application in an active volcanic crater is to detect the influence of gas emission and local atmospheric change into the accuracy of measurement.The measurement was conducted at Papandayan Volcano crater, along with the local temperature, humidity, and air pressure (thp). The measured target located near a gas emission hole gives a significant fluctuative range due to possible false return by gas particles. The refraction index was calculated using thp data. Two correction models were applied: velocity-geometry and atmospheric delay correction. The atmospheric delay correction gives a more reliable result, however their refraction index calculation does not accomodate specific volcanic gas yet. An intensity map obtained from TLS can also be used for rock segmentation. An experiment from some types of volcanic rocks shows that the intensity value is influenced by a weathering degree of rock outcrops. Rock segmentation using TLS intensity data for fresh outcrops is relatively easier, while for weathered rocks it still needs a field check for validation. The temperature of volcanic rocks also contributes to the intensity value. It is found that the intensity increases along with the temperature of rock.